Assessment of vulnerability to natural hazards : a European perspective - Birkmann, Jörn; Kienberger, Stefan; Alexander, David 1953- (Elsevier, 2014)
"Reducing risk that emerges from hazards of natural origin and societal vulnerability is a key challenge for the development of more resilient communities and the overall goal of sustainable development. Newest global assessment reports (GAR 2011, Welle et al. 2012; IPCC 2013) underscore that risk reduction and resilience building remains a key challenge for developing and developed countries alike particularly due to the increasing exposure of people and assets in high risk zones and the intensification of extreme events in the context of climate change (see e.g. IPCC 2013). It is increasingly recognized that natural hazard associated risk and threats to human security cannot be reduced by focusing solely on the hazards. Societies will have to live with changing environmental conditions and therefore need to build resilience by reducing vulnerabilities to natural hazards. Vulnerability assessment of natural hazards and climate change has emerged in the past decades as an important research field (see e.g., Maskrey, 1984; Chambers, 1989; Pelling, 1997; Cardona, 2001; Birkmann, 2006a/b; Adger, 2006; IPCC, 2007; Bohle, 2008; Bohle and Glade, 2008; Oxfam America, 2009, Birkmann 2013) bringing together scientists from different disciplines (Fuchs, 2009)"--Resumé vydavatele
Keywords: přírodní katastrofy -- Evropa; environmentální rizika -- Evropa; krizový management; civilní ochrana; havarijní plánování; natural disasters -- Europe; environmental risk -- Europe; crisis management; disaster planning; civil defence; kolektivní monografie; elektronické knihy; collective monographs; electronic books